2011
DOI: 10.1038/sj.bjc.6606093
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter phase II study of induction chemotherapy with FOLFOX-4 and cetuximab followed by radiation and cetuximab in locally advanced oesophageal cancer

Abstract: Background:Preoperative chemoradiotherapy (CRT) improves the survival of patients with oesophageal cancer when compared with surgery alone.Methods:We conducted a phase II, multicenter trial of FOLFOX-4 and cetuximab in patients with locally advanced oesophageal cancer (LAEC) followed by daily radiotherapy (180 cGy fractions to 5040 cGy) with concurrent weekly cetuximab. Cytokines levels potentially related to cetuximab efficacy were assessed using multiplex-bead assays and enzyme-linked immunosorbent assay at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 26 publications
3
22
0
Order By: Relevance
“…However, most patients are diagnosed with locally advanced tumors, regional lymph node involvement, or metastatic disease (14). Clinical trials have attempted to improve the clinical outcome by reducing the rate of local disease recurrence through integrating radiotherapy and chemotherapy in patients with ESCC, but a clear benefit has never been achieved (15,16). Thus, development of adequate screening techniques and effective novel therapeutic regimens are urgently needed.…”
Section: Discussionmentioning
confidence: 99%
“…However, most patients are diagnosed with locally advanced tumors, regional lymph node involvement, or metastatic disease (14). Clinical trials have attempted to improve the clinical outcome by reducing the rate of local disease recurrence through integrating radiotherapy and chemotherapy in patients with ESCC, but a clear benefit has never been achieved (15,16). Thus, development of adequate screening techniques and effective novel therapeutic regimens are urgently needed.…”
Section: Discussionmentioning
confidence: 99%
“…Chemoradiation regimens using paclitaxel (Goldberg et al, 2003;Bains et al, 2002;Orditura et al, 2010;Ruppert et al, 2010), docetaxel (Pasini et al, 2005;Spigel et al, 2010), irinotecan (Ruppert et al, 2010;Ilson et al, 2002;Watkins et al, 2011;Sun et al, 2011), oxaliplatin (Spigel et al, 2010;De Vita et al, 2011;Chiarion-Sileni et al, 2009), epirubicin (Sun et al, 2011) and pemetrexed (Jatoi et al, 2010) have shown encouraging results. Biologic agents, such as cetuximab, trastuzumab, erlotinib, celecoxib and bevacizumab (De Vita et al, 2011;Safran et al, 2002;Enzinger et al, 2003;Suntharalingam et al, 2006) are being used as the foundations for new regimens which may enhance chemoradiation and target systemic micrometastases. Whether these investigational approaches offer improved results compared to conventional chemoradiation regimens based on 5-FU and cisplatin is not known.…”
Section: New Combined Modality Regimensmentioning
confidence: 99%
“…Finally, a trial centered at Brown University is evaluating the rate of complete pathologic response as determined by surgical resection or post treatment endoscopy (for patients not undergoing resection) for the treatment regimen being tested (NCT00439608). While cetuximab administered as a single agent had minimal clinical activity in patients with advanced esophageal cancers, these ongoing phase 2 clinical trials of EGFR inhibitors in combination with other agents may define a role for these agents in the treatment [37,38].…”
Section: Clinical Trial For Targeting Egfr-imentioning
confidence: 99%